2020
DOI: 10.1519/jsc.0000000000003788
|View full text |Cite
|
Sign up to set email alerts
|

Positive Relationships Between Golf Performance Variables and Upper Body Power Capabilities

Abstract: The importance of lower body and trunk strength and power, as well as upper body strength in golf is well documented, however the relationship between upper body power and golf performance has yet to be determined. Therefore, the purpose of the study was to investigate the relationships between golf performance and upper body power. Thirteen golfers (mean ± SD: age: 30 ± 7 years and handicap: 6.1 ± 4.9) participated in the study. Club head velocity (CHV) and ball velocity were measured during the golf test. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…A range of improvements have been observed for CHV and carry distance, Doan et al (2) identified a 1.6% increase in CHV with Lephart et al (20) and Fletcher et al (15) showing improvements of 1.5 -5.2% and 4.3 -7.7% for CHV and carry distance respectively. Additionally, strong relationships have been identified between upper body power capabilities and golf performance (CHV and ball velocity) (21). Based on these results golf driving performance is enhanced by improving power capabilities of the golfer.…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…A range of improvements have been observed for CHV and carry distance, Doan et al (2) identified a 1.6% increase in CHV with Lephart et al (20) and Fletcher et al (15) showing improvements of 1.5 -5.2% and 4.3 -7.7% for CHV and carry distance respectively. Additionally, strong relationships have been identified between upper body power capabilities and golf performance (CHV and ball velocity) (21). Based on these results golf driving performance is enhanced by improving power capabilities of the golfer.…”
Section: Introductionmentioning
confidence: 83%
“…Prior to measuring golf performance variables, all participants completed a standardized warm up. This consisted of dynamic stretches targeting lower and upper body structures, as well as practice swings and full golf shots (21). Participants then performed 8 golf shots with the Driver, with 30-seconds rest in between each trial (36).…”
Section: Golf Drive Performancementioning
confidence: 99%
“…In terms of lower body power, previous studies have reported significant associations with CHS including countermovement (CMJ) positive impulse (r = 0.70-0.79, p < 0.05) [4,11] and peak power (r = 0.61, p < 0.05) [10]. From an upper body power perspective, field-based testing has shown significant associations between CHS and rotational medicine ball throws (r = 0.62 and 0.56 for males and females, respectively, p < 0.05) [5] and ball speed and ballistic bench press peak power (r = 0.66, p < 0.05) [14]. Collectively then, it appears that moderate to large positive associations are evident between measures of lower and upper body strength and power and important golf performance measures such as CHS and ball speed.…”
Section: Introductionmentioning
confidence: 99%
“…Upper-body strength-related measures (e.g., maximal strength; rate of force development), and anthropometric characteristics, have been shown to differentiate sub-elite and elite athletes [1,2]. Research has also demonstrated the positive relationship between upper-body power measures, such as bench press throws and upper-body Wingate test [3,4], and strength measures, such as the bench pull, bench press, and pulldown test [5][6][7][8], with athletic performance in various sports, including golf, rugby, handcycling, (sprint) swimming, double poling, and (sprint) kayaking. Furthermore, markers of upperbody strength, such as one repetition maximum (1RM) for the bench press and bench row or handgrip strength, have proven to be useful for identifying talented athletes in kayaking, cross-country skiing, and tennis [9][10][11].…”
Section: Introductionmentioning
confidence: 99%